Pertumbuhan dan Perkembangan Jamur Tiram Putih (Pleurotus ostreatus) pada Media Ampas Sagu - Choliq Kurniawan; Imam Widodo; Barahima Abbas (Cassowary, 2021)
White oyster mushroom (Pleurotus ostreatus) is currently quite popular and much loved by the public because of its delicious taste, high protein content, and low fat. This study aims to measuring the growth of white oyster mushrooms grown on sago dregs media with the treatment of various supplements, measuring the growth power of oyster mushrooms on sago dregs media with the treatment of various kinds of supplements, and measuring the production and efficiency of white oyster mushrooms on the substrate used. This research method consisted of 12 treatments and was repeated 3 times, so that there were 36 experimental units. Research Results White oyster mushrooms grown on MS2 media composition (20 g + MS 80 ml dry sago pulp) showed a good effect on mycelium growth and harvest rapidly. The highest number of fruit bodies was produced in the A3 treatment (20 g of dry sago pulp + 100 ml of water). The highest body weight of fresh mushroom fruit was in the K3 treatment (20 g dry sago pulp + 100 ml coconut water), KN3 (20 g dry sago pulp + 100 ml KN), KN1 (20 g dry sago pulp + 60 ml KN) , and A3 (20 g of dry sago pulp + 100 ml of water). The efficiency of utilization of sago waste organic matter by white oyster mushrooms was 25.84%.